Not only blonde hair - Paulesu, Federico (Psihološka obzorja (Ljubljana), 2024)
Women are affected from the so-called Gender Science Stereotype (GSS) according to which they are always considered as less competent than men in scientific fields for the only reason of being women, hence being obstacled and discriminated while pursuing that career. The scope of this study is to test whether some well-known stereotypes, such as the ‚dumb blonde‘ (i.e., blonde women are considered dumb or naive), could explicitly effect the GSS and how they interact with each other. To investigate this, we manipulated pictures of a woman (Exp. 1) and a man (Exp. 2), by modifying (i) hair colour; (ii) hair length; (iii) glasses and (iv) make-up (Exp.1 ) or beard (Exp. 2), obtaining in this way 36 pictures for each experiment (3x3x2x2). Each picture was presented twice, once associated with a scientific text and once with a novel. Here we are presenting preliminary data, where participants (n = 45) were asked to evaluate, on a 10-points Likert scale, the authorship’s likelihood. Results show a negative effect of blonde hair (‘’dumb blonde’’) for both genders and heavy make-up for women, as well as a positive effect of glasses for both genders and of beard for men. Interestingly, although no gender-science stereotype has been found for women (Exp. 1), this emerged in Exp. 2. The interaction between scientific genre and make-up for women show that this stereotype is present when enhanced by other factors, such as the “highly” feminising effect of make-up. These results are discussed considering both perceptual and social theories.
Keywords: blonde hair; gender bias; ličila; make-up; social perception; socialno zaznavanje; spolna pristranskost; stereotipi; stereotypes; svetli lasje